Structural approach for improving english writing skills among students of tenth year “a” of basic education afternoon session, at “unidad educativa padre Julián Lorente” in loja city, during the 2020-2021 academic period - Vera Romero, Fabricio Alexander (2021)
The present research work aimed to improve writing skills through the use of the Structural Approach among the students of the tenth year "A", afternoon session, at Unidad Educativa Padre Julian Lorente, in the city of Loja during the 2020-2021 academic period. For the fulfillment of this objective, the methods used were: the scientific, descriptive, analytical-synthetic and statistical, which were useful for obtaining theoretical information on the strategy, for the description of the problem; tabulate, process and present the data obtained in tables and figures and to analyze and interpret the information. Tests and questionnaires were the instruments applied to the 14 students to diagnose their writing skills and their thoughts towards the strategy. The results show that, through the application of the structural approach, the students achieved a great improvement in their writing in relation to grammatical structures, grammatical gradation and word order. Concluding, this strategy made students become more confident and participative during the classes. They now not only corrected themselves but also helped their partners when they made a mistake.